PENGARUH PEMBERIAN ARANG TERHADAP PERTUMBUHAN TANAMAN CABAI MERAH (Capsicum annum) - Gusmailina Gusmailina; Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
The experiment has been conducted on utilizing different types of charcoal as growth-stimulating agents by adding each of them to the growing media (i.e. soil stuff) of red pepper plant; and subsequently evaluating their effects on its growth characteristics/ responses. There were three types of agents used and added to the media, i.e. rice-husk charcoal, bamboo charcoal, and sawdust-mixed charcoal. respectively. For comparative purposes, were also measured the growth responses of the red pepper plant whereby its growing media were added with compost as well as the Bokasi rice-husk charcoal compost, besides the ones in the medium without the addition of any growth agents (as control). This experiment revealed some remarkable results. as follows:• Additions of 5 % bamboo charcoal or l 0 % rice-husk charcoal could increase the height growth of the red pepper plant, in comparison with the one grown on the control medium:• Additions of 10 % rice-husk charcoal could increase the stem diameter of the plant by 11 % compared to the one on the control medium;• Likewise, additions of 5 % and 10 % sawdust-mixed charcoal could each increase the stem diameter by consecutively l1 % and 10 %, in comparison with the control;• Additions of 10 % bamboo charcoal brought about the best effect with respect to the increase in the number as well as the weight in red-pepper fruits in their first harvest (i.e. 3-month age), compared to the control:• Additions of 10 % rice- husk charcoal, 5 % bamboo charcoal, and 10 % sawdust-mixed charcoal each brought about also the best effect with respect to the increase in the dry weight of the plant, i.e.consecutively 2.0, 2.0, and 1.8 times as such as that of the control;• Average amount of C02 absorbed by the red- pepper plants for 3 months was 0.10-0.88 gram per plant. The highest C02 absorption was achieved by the corresponding plants with addition of 10 % sawdust-mixed charcoal (i.e. 1.88 gram C02 per plant), followed in decreasing order by the ones added with 10% rice-husk charcoal and 10 % bamboo charcoal (i.e. 1.67 gram C02per plant and 1.34 gram C02 per plant, respectively).